2011
DOI: 10.1007/s10641-011-9949-1
|View full text |Cite
|
Sign up to set email alerts
|

Diel variation in use of cover and feeding activity of a benthic freshwater fish in response to olfactory cues of a diurnal predator

Abstract: Some fish recognize the threat of predatory fish through chemical cues, which may result in variation in diel activity. However, there is little experimental evidence of diel shifts in activity of prey fish in response to the diel activity of a predator. We compared the total prey consumed and the use of cover by common bullies (Gobiomorphus cotidianus), a native benthic feeding eleotrid, when exposed to the odour of an exotic predator, European perch (Perca fluviatilis), over a 12-h period. Our results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
8
0
2
Order By: Relevance
“…Nevertheless, hatchery‐reared fish displayed a significantly lower night‐time activity, while wild fish did not. The more intense nocturnal movement of wild fish may be connected with feeding and predator avoidance (Vanderpham et al , ); this difference has been noted for related species, such as for S . trutta (Diana et al , ) and Atlantic salmon Salmo salar L. 1758 (Fraser et al , ).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, hatchery‐reared fish displayed a significantly lower night‐time activity, while wild fish did not. The more intense nocturnal movement of wild fish may be connected with feeding and predator avoidance (Vanderpham et al , ); this difference has been noted for related species, such as for S . trutta (Diana et al , ) and Atlantic salmon Salmo salar L. 1758 (Fraser et al , ).…”
Section: Discussionmentioning
confidence: 98%
“…For example, the response of bullies to predators has been studied using water scented with shortfin eel Anguilla australis (i.e., a native predator; Hammond‐Tooke, Nakagawa, & Poulin, ) and perch Perca fluviatilis (i.e., an introduced predator; Vanderpham, Nakagawa, & Clossy, ). Vanderpham et al () showed that G. cotidianus utilized shelter (i.e., PVC tubes) more in the dark when a predator odour was present compared to the control, but contrary to their predictions there was no difference between control and odour treatments in light conditions. The authors proposed that perhaps the lack of visual cues in addition to predator odour produced the unexpected results.…”
Section: Discussionmentioning
confidence: 99%
“…; Vanderpham et al. ). In our analysis of lateral‐line system morphology, we have only included total oculoscapular canal pores, as no habitat‐related patterns of variation in dorsal head superficial neuromasts were found in previous research (Vanderpham ).…”
Section: Methodsmentioning
confidence: 99%